CONDENSATION FROM SUPERNOVA GAS MADE OF FREE ATOMS - Ebel D.S.; Grossman L. (My University, 2001)
Silicon carbide grains and graphite spherules containing TiC inclusions are found in the Murchison carbonaceous chondrite. The high 44Ca (from 44Ti) and 28Si contents of these grains are strong evidence that all three minerals originated in the deep zones of Type II supernova ejecta. We present equilibrium calculations for SN shells, and show that TiC, but not graphite or SiC, is a stable condensate in the innermost shells where [Ti + Si] >> [C + O], even though C/O < 1 in these shells. Because of the great stability of gaseous CO, however, neither carbides nor graphite can survive at chemical equilibrium in the massive O-rich shells which separate the heavy element-rich inner sources of 44Ti and 28Si from outer C-rich zones where these minerals would be stable. Clayton et al. (1999) found that, under circumstances where all gaseous molecules and particularly CO are completely dissociated by Compton electrons, specific choices of kinetic parameters enable the prediction of graphite formation, even in an O-rich supernova shell. Following up on this hypothesis, we calculated high-temperature equilibrium condensation sequences in the absence of polyatomic molecules for gases having canonical solar, and supernova shell compositions. Graphite is indeed predicted to be stable in O-dominated supernova zones in the absence of gaseous molecules. But the complementary phases found in meteorites, TiC and SiC, are not stable under these conditions, while SiO2, which is not found, is produced in abundance. Without resolving these discrepancies between theory and observation, the problem of reconciling the zone where the mineralogical identities of supernova grains were established with the zone implied by their isotopic compositions remains unsolved.